Green information technology adoption towards a sustainability policy agenda for government-based institutions: an administrative perspective - Anthony Jnr, Bokolo; Mazlina, Abdul Majid; Awanis, Romli (Emerald Insight, 2018)
Purpose – The purpose of this study is to identify the key Green information technology (IT) components needed to be considered by government-based institutions and to develop a Green policy framework based on the identified Green IT components to facilitate government-based institutions achieve sustainability. Design/methodology/approach – The Green policy framework and associated propositions are developed to facilitate government-based institutions achieve sustainability. In addition, a case study approach was adopted to verify the proposed framework based on data collected from openended interviews and sustainability report documents from two government-based institutions in Malaysia. Furthermore, the collected data were analyzed based on content analysis using descriptive and narrative method to present the findings of Green IT components adopted in the selected case studies. Findings – Findings show that sustainability considerations are increasingly being deliberated in institutions. Moreover, finding from the analyzed data also indicates that there is an increased interest towards implementation of Green IT initiatives for developing, operating and usage by practitioners and staff within government-based institutions. Research limitations/implications – Findings from this study suggest that the Green policy framework components have implications to support only government-based institutions address environmental, social and economic-related issues. Practical implications – The developed Green IT components serve as robust indicators or constructs to measure management of Green IT initiatives currently being implemented and thereby provide a framework for sustainability committee members to benchmark their current Green IT practice. Social implications – This study provides an agenda to guide government-based institutions achieve sustainability goals. Accordingly, government-based institutions can adopt the framework’s components to evaluate their progress, hence improving their target of attaining sustainability. Besides, this research provides an approach for assessing current practices adopted in government-based institutions against the Green IT components. Originality/value – The originality of this study is attributed to the fact that this study presents Green IT policy framework to be considered by government-based institutions in achieving sustainability. The framework provides an agenda to simultaneously consider all three dimensions of sustainability the people, planet and profit (social, environment and economic). Moreover, this is one of the first studies to explore Green IT practices in government-based institutions.